CRM Tizimining Afzalliklari - Dexkonov Tavakkaljon Alimjanovich (Peerian Journals Publishing, 2022)
CRM is such a tool that allows you to store contact information with customers or partners, identify sales opportunities, identify service problems, and manage marketing campaigns. When the program starts, all contacts and contact information, inter-interview, agreements, sales efficiency and its results are located in the same center, and the ability to quickly and easily find and use information about any interactions with customers will be possible.
Keywords: CRM; client; privilege; payment